Gansu Tianxing Rare-Earth Functional Materials Co., Ltd. (Физика низких температур, 2001)
GaTianxingTi (for short), founded in June 1998 by Chen Zheng (Chairman of the Board), is a private company. It’s self-funded, self-financed, and self-managed with fixed asset of about US$ 16 million.